PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS SMART APPS CREATOR UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK DI SEKOLAH DASAR - Choirunisa Amalia; Trian Pamungkas Alamsyah; Aan Subhan Pamungkas (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2022)
This research is motivated by the low ability of students to understand mathematical concepts, and the lack of use of technology in the learning process. This study aims to determine the feasibility of learning media, and to determine the extent to which students' understanding of mathematical concepts has increased after using the developed Smart Apps Creator-based mathematics learning media. The method used in this study is Research and Development (R&D) with the development model being the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This study resulted in learning media based on Smart Apps Creator (android application) on mixed arithmetic operations with whole numbers as the subject of research, students of class VI SDN Margahayu IX Bekasi City. The results of the study found that the learning media developed was